The Role of Physical Activity in Managing Urological Health: A Review with Focus on Prostate Cancer and Overactive Bladder, Including Related Conditions - Bigajski, Hubert; Banaś, Aleksandra; Michalik, Maciej; Widera, Piotr; Handschuh, Marta; Bilczewska, Olga; Helis, Justyna; Janik, Wiktoria; Jakubczyk, Paulina; Buczek, Aleksandra (Quality in Sport, 2025)
Introduction and Purpose This review explores physical activity’s role in managing urological health, focusing on prostate cancer and overactive bladder (OAB). These conditions significantly affect quality of life globally. The review synthesizes research to identify gaps and propose future directions for clinical practice. Materials and Methods A literature search was conducted using PubMed, MEDLINE, and Cochrane Library databases (2010-2023). The focus was on randomized controlled trials, observational studies, and systematic reviews. Key terms included "physical activity," "prostate cancer," "overactive bladder," and "urological health." Studies were selected based on relevance to exercise interventions in urological conditions. Results High-intensity exercise reduces prostate cancer risk by 10–30% and improves outcomes by enhancing cardiovascular fitness and quality of life. For OAB, low-impact aerobic exercises alleviate symptoms by improving neuromuscular control and reducing inflammation. Mechanisms include hormonal regulation, improved metabolic health, and reduced inflammation. Structured prehabilitation programs with pelvic floor muscle training optimize continence outcomes post-surgery. Conclusions Physical activity is a cost-effective intervention for managing urological health. Despite strong evidence supporting its benefits, gaps remain in understanding optimal exercise prescriptions and long-term effects across diverse populations. Future research should focus on tailoring interventions to patient needs, exploring innovative modalities like high-intensity interval training, and integrating exercise with other treatments to improve outcomes.